2022
DOI: 10.1080/21645515.2022.2065167
|View full text |Cite
|
Sign up to set email alerts
|

The association between social media use and hesitancy toward COVID-19 vaccine booster shots in China: A web-based cross-sectional survey

Abstract: COVID-19 vaccine booster shots are necessary to provide durable immunity and stronger protection against the emerging SARS-CoV-2 variants. As a major platform for access to information, social media plays an important role in disseminating health information. This study aimed to evaluate hesitancy toward COVID-19 vaccine booster shots in China, assess its association with social media use, and provide information to manage social media. We conducted a cross-sectional study across all 31 provinces in mainland C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 43 publications
(36 reference statements)
2
26
0
1
Order By: Relevance
“…A large-scale nationwide survey conducted in China found that only 10.56% (30/284) of older adults (≥60 years old) were hesitant about receiving a booster shot ( 38 ), whereas in Jordan and Bangladesh (≥50 years old), the rates were 35.0 and 44.6%, respectively ( 20 , 41 ). In addition, time spent on social media tracking news about COVID-19 and vaccines was also associated with vaccination acceptance ( 42 ). Our study also reflected the positive effect of vaccination history on receiving the booster shots, which was consistent with previous studies ( 19 , 21 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A large-scale nationwide survey conducted in China found that only 10.56% (30/284) of older adults (≥60 years old) were hesitant about receiving a booster shot ( 38 ), whereas in Jordan and Bangladesh (≥50 years old), the rates were 35.0 and 44.6%, respectively ( 20 , 41 ). In addition, time spent on social media tracking news about COVID-19 and vaccines was also associated with vaccination acceptance ( 42 ). Our study also reflected the positive effect of vaccination history on receiving the booster shots, which was consistent with previous studies ( 19 , 21 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another surprising result was that, among older adults, the higher the knowledge scores on COVID-19 vaccines, the lower the willingness to take booster shots. More efforts are needed to regulate social media content and filter out misinformation ( 42 , 43 ). The role of official social media in disseminating health information should be strengthened ( 42 , 43 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge about the COVID-19 and COVID-19 vaccines may also influence older adults’ attitudes toward the booster shots. 27 Therefore, a total of 10 items (23 points) were set to evaluate the knowledge level of participants. The sources of infection, transmission routes, high-risk groups, prevention and control measures, vaccine effectiveness, and other important precautions were all included in this section.…”
Section: Methodsmentioning
confidence: 99%
“…With the promotion of various media and government policies, the COVID-19 vaccination rate in China is impressive, but further efforts are still required. Current studies reported many factors that contributed to COVID-19 vaccine hesitancy, such as the concerns of effectiveness, safety and the vague side-effect about the existing vaccine (12)(13)(14)(15). COVID-19 vaccine hesitancy presented to be a noteworthy public health issue.…”
Section: Introductionmentioning
confidence: 99%